2016
DOI: 10.1007/978-3-319-18497-5_3
|View full text |Cite
|
Sign up to set email alerts
|

Human Data Supporting Glyburide in Ischemic Stroke

Abstract: The SUR1-TRPM4 channel is a critical determinant of edema and hemorrhagic transformation after focal ischemia. Blockade of this channel by the small molecule glyburide results in improved survival and neurological outcome in multiple preclinical models of ischemic stroke. A robust, compelling body of evidence suggests that an intravenous (IV) formulation of glyburide, RP-1127, can prevent swelling and improve outcome in patients with stroke. Retrospective studies of diabetic stroke patients show improved outco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 31 publications
0
22
0
Order By: Relevance
“…Currently, sulfonylureas such as glibenclamide have been shown to be promising TRPM4 blockers. TRPM4 has been reported to form a channel complex with sulfonylurea receptor-1 (SUR1), an auxiliary subunit of K ATP channel [ 15 ], and SUR1 blocker sulfonylureas have been used to treat brain diseases such as stroke [ 20 ]. However, there is controversy regarding the regulatory role of SUR1 on TRPM4 and the effect of sulfonylureas in stroke treatment [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, sulfonylureas such as glibenclamide have been shown to be promising TRPM4 blockers. TRPM4 has been reported to form a channel complex with sulfonylurea receptor-1 (SUR1), an auxiliary subunit of K ATP channel [ 15 ], and SUR1 blocker sulfonylureas have been used to treat brain diseases such as stroke [ 20 ]. However, there is controversy regarding the regulatory role of SUR1 on TRPM4 and the effect of sulfonylureas in stroke treatment [ 21 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, SUR1 blocker sulfonylureas are widely used to manage diabetes mellitus. Multiple studies on stroke patients with or without diabetes mellitus revealed that use of sulfonylureas before or after stroke onset could reduce hemorrhage transformation, attenuate cerebral edema, and improve neurological outcome [ 20 , 22 ]. In contrast, some studies on diabetic patients with stroke showed that application of sulfonylureas achieved no better outcome than other anti-diabetic treatments [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is possible that Sur1-Trpm4 channel-induced neuropathological effects are responsible for the Vpr effects or are part of the collective induction of Vpr-induced HAND. If this is true, this finding might be clinically significant because the Sur1-Trpm4 channel has shown to be a key drug target of various neuroinflammatory conditions 21,[37][38][39][40][41] , and pharmacologic inhibition of this channel by the repurposed and FDA-approved drug glibenclamide significantly improved clinical outcomes of those neurologic disorders 21,[42][43][44][45] . Indeed, the Sur1 inhibitor glibenclamide suppresses Vpr-induced apoptosis in a concentration-dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, we may have uncovered a novel HAND-underlying mechanism involving Vpr-induced activation of the Sur1-Trpm4 channel. Once substantiated, it would allow us to test the possibility of treating HAND-afflicted individuals by using the FDA-approved Sur1 inhibitory drug glibenclamide, which has already been shown to be an effective drug for treatment of various neurological disorders 21,[42][43][44][45] . Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Glibenclamide preferentially blocks the Sur1-Trpm4 ion channel that is upregulated in damaged central nervous system tissue, and has shown promise in preclinical SCI studies as well as recent promising results in phase II of a clinical trial for treatment of malignant ischemic stroke. 67 Glibenclamide compared favorably to hypothermia, and both were superior to riluzole in terms of safety and efficacy. Thus, given the relative ease of drug delivery versus perioperative systemic hypothermia, perhaps glibenclamide may become a treatment option pending further clinical trial data, as a pilot safety study is now recruiting SCI patients (NCT02524379).…”
Section: Other Treatmentsmentioning
confidence: 91%